2016
DOI: 10.2147/ijn.s105681
|View full text |Cite
|
Sign up to set email alerts
|

The spherical nanoparticle-encapsulated chlorhexidine enhances anti-biofilm efficiency through an effective releasing mode and close microbial interactions

Abstract: We reported two forms (sphere and wire) of newly fabricated chlorhexidine (CHX)-loaded mesoporous silica nanoparticles (MSNs), and investigated their releasing capacities and anti-biofilm efficiencies. The interactions of the blank MSNs with planktonic oral microorganisms were assessed by field emission scanning electron microscopy. The anti-biofilm effects of the two forms of nanoparticle-encapsulated CHX were examined by 2,3-bis (2-methoxy- 4-nitro-5-sulfo-phenyl)-2H-tetrazolium-5-carboxanilide. The profiles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…The biofilms were then treated with TC (0.5, 0.75 and 1%), NaOCl, CHX, DMSO or deionized water for 5 and 15 min. The treatment solutions were then carefully aspirated, biofilms were rinsed with PBS and the biofilm viability was evaluated using the XTT metabolic activity as described previously [23]. Briefly explained, 200 µl of (XTT + menadione) reaction solution was added to each well, and incubated in dark for 3 h at 37°C.…”
Section: Short-term Treatment Of E Faecalis Biofilmsmentioning
confidence: 99%
“…The biofilms were then treated with TC (0.5, 0.75 and 1%), NaOCl, CHX, DMSO or deionized water for 5 and 15 min. The treatment solutions were then carefully aspirated, biofilms were rinsed with PBS and the biofilm viability was evaluated using the XTT metabolic activity as described previously [23]. Briefly explained, 200 µl of (XTT + menadione) reaction solution was added to each well, and incubated in dark for 3 h at 37°C.…”
Section: Short-term Treatment Of E Faecalis Biofilmsmentioning
confidence: 99%
“…In another approach to the topic, Li et al studied the effect on the morphology and size of silica nanosystems (rounded vs rod-like nanoparticles) on the delivery of chlorhexidine to several bacterial lines ( Streptococcus sobrinus, Streptococcus mutans and C. albicans ). 35 From their studies, it is demonstrated that nonmodified MSNs were able to adhere better onto bacterial walls as a consequence of the interaction between the negatively charged silica and peptidoglycans therein. Regarding particle size these authors found that even with the same functionalization, larger particles (over 100 nm) were unable to diffuse into the cytoplasm, causing not only damage at the bacterial walls, but also not a complete antibiotic effect.…”
Section: Delivery Of Antibiotic Compoundsmentioning
confidence: 99%
“…The data indicate that there was a drop in the antialgal effect of CHX when loaded within shellac NPs in comparison with effect of the free CHX, while there was a profound change in the antialgal action of the encapsulated CHX after coating the nanocarrier with ODTAB. Note that most other CHX nanocarriers reported in the literature had negative surface charges [42][43][44][45]. The cationic surface of the ODTAB-coated NPs attracts them to the negatively charged algal cell membrane and subsequently delivers higher loads of CHX ions on their membranes.…”
Section: Antialgal Activity Of Odtab-coated Chx-loaded Shellac Nps On C Reinhardtiimentioning
confidence: 99%